Keterampilan Digital: Pengaruh Kompetensi Digital terhadap Minat Bisnis Online - Andriansyah, Andriansyah; Ernawati, Ernawati; Herman, Herman; Budi Rahayu, Pramudita (Jurnal Pekommas, 2024)
The importance of this research lies in the inevitability of today's digital technological advancements, marking a period where prioritizing work efficiency and effectiveness has become essential, giving rise to what is known as the digital age. A large number of younger individuals are captivated by the complexity of technology, often using it solely for recreational purposes. The impact of such behavior stems from the inappropriate utilization of technology, potentially turning the next generation into mere consumers in a consumer-driven society. The younger generation must be more digitally savvy so as to encourage the utilization of digital technology to be more productive in order to foster the seeds of reliable and skilled young business people who are technologically literate. Digital competence is not only understanding the hardware of a technology, but also the software, and it is inseparable. The purpose of this study is to determine the influence between the digital competence of the young generation of Makassar city on online business interest, as well as what factors that are supporting and inhibiting. The method used was through a quantitative approach which was analyzed through validity, reliability, normality, linearity and simple liner regression tests with the help of the SPSS version 24 application. The respondents of this study were 222 teenagers in Makassar City. The results of the study state that there is a significant influence between digital competence on interest in doing business online by 39.3%, and 60.7% is influenced by other factors. The supporting factors for adolescents include the ability to use hardware such as gadgets/smartphones that are high, as well as the ability to search for information online, while the obstacles are the lack of ability to use commerce platforms and the lack of interest to start an online business, moreover reluctant to run it. Other factors that influence interest in doing business online include the availability of the capital, fear of bearing the risk of failure, etc. The limitations in this study are the lack of respondents who filled out questionnaires and still need to be researched on aspects of adolescent psychology.